PRAGMATIC MARKER AS A LANGUAGE POLITENESS MITIGATING DEVICE IN TALK SHOW ON SPIRITUAL GENRE - Husna Faredza Mohamed Redzwan, Anida Sarudin, Khairul Azam Bahari, Zulkifli Osman (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
High level social communication skill involving language politeness is important in communications and as such, it cannot be ruled out. As such, this paper aimed to explore the function of the ya pragmatic marker as a tool for language politeness as well as its relationship with the usage of the language politeness strategy from the pragmalinguistic aspect. In this study, the researcher used the religious talk show programme hosted by ustazah (female religious teachers) in the context of examining the pragmatic marker. The particular religious talk show programme was produced by TV9 and it was titled Tanyalah Ustazah with the topic The Decency in Facing Difficulty ‘Kebaikan dalam Masalah’. The data acquired was then transcribed to enable the analysis process. The data was processed using the AntConc 3.2.4w software and later it was analysed using a qualitative method. Additionally, the ya pragmatic marker was also described based on the contemporary and authentic corpus data. The analysis was conducted using Brown and Levinson’s Politeness Theory (1987). The findings showed that the ya pragmatic marker in the religious talk show genre could function as a language politeness device.